Turbocharging fundamental science translation through controlled environment agriculture - Alison R. Gill; Troy K. Miller; Samalka Wijeweera; Eva Herrero; Gioia D. Massa; Jenny C. Mortimer; Alex A.R. Webb; A. Harvey Millar; Matthew Gilliham (Trends in Plant Science, 2026)

Differential metabolomic effects of progestagen-based estrus synchronisation in South African Dohne Merino ewes - R. Shingange; C. Visser; M. Wooding; E. C. Webb (Tropical Animal Health and Production, 2026)
This study represents one of the first to comprehensively profile the homeostatic cervicovaginal metabolome of South African Dohne Merino ewes using liquid chromatography high resolution mass spectrophotometry (LC-HRMS) and compare that metabolome immediately after estrus synchronisation using progestagen intravaginal pessaries. As the use of assisted reproductive technologies gains traction in various livestock production systems, characterising their effects using novel omics approaches is crucial to physiology, welfare and production. An ewe has well-developed metabolomic cascades that are homeorhetically responsive to the stress caused by assisted reproductive treatments in order to maintain homeostasis. The cervicovaginal fluid of sixty ewes was sampled by transvaginal FLOQSwabs before pessary insertion as well as immediately post-pessary removal. These swabs, along with field, solvent and swab blanks, underwent extraction in acetonitrile and drying under nitrogen prior to reconstitution. Using one-way ANOVA with Tukey’s HSD post-hoc analysis and PERMANOVA, this study found no significant metabolomic features prior to treatment ( P > 0.05). However, after pessary removal, 32 features were reported to be different between the CIDR-, sponge-treated and control group ( P < 0.005 and False Discovery Rate < 0.05). Features were identified at four levels including at verification with pure chemical standards. Progesterone was found to be highest in the CIDR-treated group ( P < 5.0 × 10 − 48 ) while linolenic acid, an immune modulator, was highest in the sponge-treated group ( P < 5.0 × 10 − 3 ). These findings present a novel understanding of the metabolomic fluctuations that occur within the cervicovaginal microenvironment in response to progestagen synchronisation protocols, which are a routine part of management in the production systems of sheep and various other species of livestock. These stark metabolomic differences highlight endocrine and immune changes that are triggered by the CIDR or sponge and warrant further characterisation of the physiological and welfare implications of these technologies.

The unpredictability of community priorities in planning for water-scarce futures in the Goulburn-Broken River Basin - Madeline A. Grupper; Avril C. Horne; Julian D. Olden; J. Angus Webb; Serene Ho (Environmental Science & Policy, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Post-prandial acyl ghrelin infusion in heart failure patients increases gastric emptying rate - Dominic-Luc Webb; Camilla Hage; Ulrika Ljung-Faxén; Gianluigi Pironti; Tonje Thorvaldsen; Daniel C. Andersson; Marcus Ståhlberg; Lars H. Lund; Per M. Hellström (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Acyl ghrelin increases cardiac output (CO) and contractility in patients with heart failure with reduced ejection fraction (HFrEF). In healthy humans, acyl ghrelin increases gastric emptying rate (GER) and hunger, a potential add-on benefit for HFrEF patients suffering from cachexia with symptoms of delayed gastric emptying and loss of appetite. The aim of this study was to determine if post-prandial acyl ghrelin infusion increases GER and hunger in HFrEF patients compared to CO. HFrEF patients ( n = 29) arrived fasted and received a 500-kcal breakfast followed by 1.5 g paracetamol. They next received placebo (vehicle, n = 15) or acyl ghrelin infusion (0.1 µg/kg/min, n = 14) for 120 min. Blood was tapped for plasma at 0, 30, 60, 120, and 150 min into the meal. Hunger scores and CO were recorded. Plasma paracetamol was measured to assess GER. Paracetamol concentration peaked at 30 min in 8 of 14 (57%) in the treatment group versus 1 of 15 (7%) in the placebo group (Mann–Whitney test, P = 0.004). Remaining patients peaked at later time points. The acyl ghrelin treatment group data was segregated into rapid (peak at 30 min, n = 8) and slow (peak > 30 min, n = 6) GER sub-groups. The rapid sub-group had an acyl ghrelin treatment effect on CO (one-way repeat measures, P < 0.001) and the highest median increase in hunger across all time points. Acyl ghrelin increases GER and in tandem with increasing CO. Effects on hunger are more difficult to resolve due to variability in subjective scores. Some HFrEF patients may benefit from this add-on effect.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Toward fully automated urban tree inventory: Integrating mobile lidar and open-source tools - Justinn J. Jones; Sorin C. Popescu; Joshuah S. Perkin; Stephen L. Webb (Urban Forestry & Urban Greening, 2026)

Early Paleozoic magmatism in the Himalaya linked with a peri-Gondwana silicic large igneous province - Dominik R. Vlaha; Andrew V. Zuza; Ariuntsetseg Ganbat; Chen Wu; Peter J. Haproff; Victor E. Guevara; A. Alexander G. Webb; Marie C. Genge; Birendra P. Singh (Tectonophysics, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Comparison of machine learning interpolation models for movement trajectories of desert bighorn sheep - John Paul C. Acosta; Seong Won Park; Dylan G. Stewart; E. Alejandro Lozano-Cavazos; Stephen L. Webb; Toryn L. J. Schafer (Environmental and Ecological Statistics, 2026)
Global positioning system (GPS) collars have revolutionized wildlife monitoring by enabling fine-scale inference of animal movement, behavior, and habitat use. However, GPS fix failures associated with terrain, canopy, or animal behavior introduce bias into downstream ecological analyses. In a study of 16 translocated desert bighorn sheep ( Ovis canadensis mexicana ) in Sonora, Mexico, we recorded 55,277 scheduled GPS fixes over 18 months, of which 720 (1.3%) were missing not completely at random with the highest rate of missingness during July (268 missing of 3720 scheduled or 7.20%). To interpolate missing locations, we evaluated five predictive models: linear regression (LM), random forest (RF), treed Gaussian processes (TGP), Bayesian additive regression trees (BART), and generalized additive models (GAM). Models were fit using temporally embedded covariates derived from environmental, temporal, and movement-related features. Random forest models achieved the highest accuracy on average (mean Euclidean distance = 54.6 m) across all individuals, outperforming BART (188.3 m), GAM (190.8 m), LM (190.6 m), and TGP (210.5 m). However, RF models also exhibited higher variability in predictive performance. Our results demonstrate that temporally embedded features capture complex behavioral and environmental dependencies, enabling accurate interpolation of GPS fixes. While RF models offer predictive advantages, post hoc averaging with lower-variance models (e.g., BART) may improve uncertainty quantification. These findings provide a demonstration of estimating a phenomenological interpolation model for subsequent animal movement analyses.

An updated Irwin sensor for measurement of surface shear velocity - Nancy P. Ziegler; Nicholas P. Webb; Brandon L. Edwards; George Nikolich; John A. Gillies; Sahil G. Patel; Brandi Wheeler; Pei Zhang; Justin W. Van Zee; Sandra L. LeGrand; Andrew C. Trautz (Aeolian Research, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

A habitability lens to boost effective local climate adaptation - A.K. Magnan; V.K.E. Duvat; J. Bell; S.D. Donner; J.D. Ford; P.D. Nunn; C. Perry; T. Spencer; C.C.C. Wabnitz; I. White; J. Butler; A. McCarthy; et al. (Environmental Science & Policy, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Hue’s in the trap? Effects of colour, time of day, and weather on the use of pitfall traps for invertebrate surveys - Anne E. Goodenough; Hannah L. Baker; Feranmi Otitolaye; Frankie Wilson; Julia C. Webb (Journal of Insect Conservation, 2026)

Evaluating a Tri-Institutional Cancer Research Capacity-Building Program for Early-Stage Investigators - Kathryn S. Maxwell; Lecarde Webb; Desiree Rivers; Ann Smith; Emily Hudson; Beverly Taylor; Shailesh Singh; Honghe Wang; Brian M. Rivers; Timothy Turner; Vivian L. Carter; Windy Dean-Colomb; et al. (Journal of Cancer Education, 2026)
The Comprehensive Partnerships to Advance Cancer Health Equity (CPACHE) initiative of the National Cancer Institute (NCI) supports long-standing collaborations between an under-resourced institution and NCI-designated Cancer Centers to strengthen cancer research workforce and advance cancer research capacity. One of the longest continuously funded CPACHE programs is the Morehouse School of Medicine/Tuskegee University/University of Alabama at Birmingham O’Neal Comprehensive Cancer Center tri-institutional partnership. A central component of this partnership is training future generations of investigators, which is accomplished through the research education programs that are designed to build cancer research skills, enhance mentorship, and support career development for all levels from high school students to Early-Stage Investigators (ESIs). This paper evaluates the longitudinal impact of a year-long program for ESIs and postdoctoral fellows since its inception in 2007. The data were extracted from the Research Education Core administrative records about the scholars and mentors and utilized publicly accessible databases Scopus and PubMed for publications, and the NIH RePORTER for grants. Among 89 program scholars, nearly 95% had at least one publication since their program start date. Of these, 70% had a first author, and 62% had a senior author publication. Approximately 20% of scholars obtained NIH funding as principal investigators through grants, core leadership, and/or supplements. This tri-institutional program successfully attracted investigators committed to cancer research. The outcomes suggest that structured training, intensive mentorship, and cross-institutional collaboration can meaningfully support their academic careers. These findings provide insights for strengthening similar programs to continue to meet the evolving professional needs for the development of ESIs and postdoctoral fellows, particularly at under-resourced institutions.

eDNA2IQI: an eDNA/random forest-based prediction tool that accurately predicts ecological status for regulatory-compliance assessment - A.J. Wyness; T. Stoeck; B.J. Morrissey; I. Berrill; K. Davidson; C. FairBairn; S. MacIntyre; C. Webb; T. Foster; S. Brain; D. Svobodova; C. Clark; et al. (Aquaculture, 2026)

Stakeholder co-design of sustainable urban pest management strategies - Elizabeth C. Lowe; Nathan J. Butterworth; Alexander Austin; Cameron Webb; Tanya Latty (Ambio, 2026)
The high levels of broad-spectrum insecticides used to manage invertebrates in many cities around the world has significant environmental and health impacts. Integrated pest management (IPM) is a framework for sustainable pest control practice, but uptake of IPM remains low in most cities. We used participatory action research with pest management industry stakeholders (practitioners, industry representatives, researchers and government employees) to identify key issues in urban pest management in Australia, set priorities for change and discuss collaborative solutions. Via an online survey and a face-to-face workshop, the participants identified the key themes of education and training, public awareness, environmental impacts and lack of IPM uptake. We present a summary of the top eight issues, the priorities identified for each one and the co-designed recommended actions that different stakeholders can take to support a shift towards more sustainable pest management practices in urban settings.

Tectonics dominates exhumation along the Himalayan arc - Jiakang Huang; Junfeng Gong; A. Alexander G. Webb; Rasmus C. Thiede; Shuang Bian; Rong Yang; Xuhua Shi; Hanlin Chen (Earth-Science Reviews, 2025)

Implications of flooding events for the green‐lipped mussels ( Perna canaliculus ): an aquatic health perspective - Joanna S. Copedo; Stephen C. Webb; Norman L. C. Ragg; Andrea C. Alfaro (New Zealand Journal of Marine and Freshwater Research, 2025)
Flood events are increasingly impacting coastal infrastructures and marine organisms. Prominent among these organisms, the green‐lipped mussel, Perna canaliculus , is an important marine ecosystem engineer and one of New Zealand’s key aquaculture species. Although relatively robust, the species may have limited capacity to tolerate acute environmental shocks such as exposure to riverine floodwater. As flood events become more frequent, they may present serendipitous opportunities for further research. Thirty days into a temperature and starvation co‐stressor experiment, a storm event resulted in the staff evacuation and eventual flooding of the research facility. Additional samples for histology were opportunistically collected after the flood waters receded, and the survival of the P. canaliculus was monitored for two weeks post‐event. Although no mortalities were observed post‐flood exposure, histological results indicate that the event did cause the mussels to spawn. Tissue conditions, such as haemocytosis of the gill and digestive gland atrophy, also appeared to be correlated with the flood event; however, the impact on P. canaliculus health was considered negligible. This research highlights not only the importance of targeted research in elucidating the impacts of climate‐related hazards on marine species but the importance of opportunistically incorporating these unforeseen events into the research.

Reduced farming density of New Zealand flat oyster Ostrea chilensis is associated with decreased infection by Bonamia ostreae and other parasites - Zoë Hilton; Anne Rolton; Farhana Muznebin; Stephen C. Webb; Andrew Fidler; Andrew Elliot; Javier Atalah; Andrea C. Alfaro; Kate S. Hutson (Aquaculture, 2025)

Establishment, current status and possible origin of the greater white-toothed shrew Crocidura russula in Great Britain - Graham C. Smith; Ian F. Bond; Terry Coult; Dan Henderson; Courtney Graham; Emma Brand; Allan D. McDevitt; Philip A. Stephens; Sophie Webb; Matt Larsen-Daw (Biological Invasions, 2025)
Great Britain has three native shrews, while the greater white-toothed shrew (GWT: Crocidura russula ) is native to the European continent and some Channel islands. The GWT shrew was first reported in northern England in 2022. We detail its immediate investigation through national authorities, non-government bodies and individuals. Sixteen GWT were among 595 small mammals live-trapped. Barn owl pellet analysis revealed 56 GWT skulls in two areas. Genetic analysis of the cytochrome b gene suggests these population were derived from one or more continental European introductions, but not from the nearby island of Ireland where this non-native species has been present since at least 2007. The overall government response from the Department for Environment, Food and Rural Affairs and Natural England concluded that the species is too widespread to have any reasonable chance of eradication, but there remain ongoing efforts to determine the extent of invasion and its effect on native species.

When is a knowledge gap filled in environmental monitoring? - Xiaoyan Dai; J. Angus Webb; Avril C. Horne; Thomas E. Wilkins (Journal of Environmental Management, 2025)

A Review of Abrupt Permafrost Thaw: Definitions, Usage, and a Proposed Conceptual Framework - Hailey Webb; Matthias Fuchs; Benjamin W. Abbott; Thomas A. Douglas; Clayton D. Elder; Jessica Gilman Ernakovich; Eugenie S. Euskirchen; Mathias Göckede; Guido Grosse; Gustaf Hugelius; Miriam C. Jones; Charles Koven; et al. (Current Climate Change Reports, 2025)
Purpose of Review We review how ‘abrupt thaw’ has been used in published studies, compare these definitions to abrupt processes in other Earth science disciplines, and provide a definitive framework for how abrupt thaw should be used in the context of permafrost science. Recent Findings We address several aspects of permafrost systems necessary for abrupt thaw to occur and propose a framework for classifying permafrost processes as abrupt thaw in the future. Based on a literature review and our collective expertise, we propose that abrupt thaw refers to thaw processes that lead to a substantial persistent environmental change within a few decades. Abrupt thaw typically occurs in ice-rich permafrost but may be initiated in ice-poor permafrost by external factors such as hydrologic change (i.e., increased streamflow, soil moisture fluctuations, altered groundwater recharge) or wildfire. Summary Permafrost thaw alters greenhouse gas emissions, soil and vegetation properties, and hydrologic flow, threatening infrastructure and the cultures and livelihoods of northern communities. The term ‘abrupt thaw’ has emerged in scientific discourse over the past two decades to differentiate processes that rapidly impact large depths of permafrost, such as thermokarst, from more gradual, top-down thaw processes that impact centimeters of near-surface permafrost over years to decades. However, there has been no formal definition for abrupt thaw and its use in the scientific literature has varied considerably. Our standardized definition of abrupt thaw offers a path forward to better understand drivers and patterns of abrupt thaw and its consequences for global greenhouse gas budgets, impacts to infrastructure and land-use, and Arctic policy- and decision-making.

Evaluating sulfurization as a blue carbon sink in a southern California salt marsh - Lena R. Capece; Melea Bailey; Max Morrison; Alexandra A. Phillips; Lewis Sharpnack; Sam M. Webb; Dana C. Brenner; Maya Gomes; Morgan R. Raven (Limnology and Oceanography, 2025)
Blue carbon ecosystems such as seagrass meadows, mangrove forests, and salt marshes are important carbon sinks that can store carbon for millennia. Recently, organic matter sulfurization and pyritization have been proposed as mechanisms of net carbon storage in blue carbon ecosystems. At our study site, organic sulfur that is resistant to acid hydrolysis (protokerogen) is an order of magnitude less abundant than pyrite sulfur, suggesting a dominance of pyritization over sulfurization. The C/N ratios and carbon isotope compositions suggest that nearly half of total organic carbon and ≥ 80% of protokerogen is composed of marsh plant material. Sediment protokerogen appears to be sulfurized based on its low δ 34 S values (− 10‰), abundance of disulfides, and higher S/C ratio (~ 1.0%) relative to potential biogenic sulfur sources. However, the interpretation of protokerogen δ 34 S values is complicated by the wide range in sulfur isotope compositions of marsh plants. Evidence for sulfurization occurs within the shallowest sediments across different vegetation zones, yielding consistent products, while pyritization appears to be more sensitive to alterations in sediment redox conditions. Based on organic sulfur and pyrite content, sulfurization may be a more spatially consistent process than pyritization, with implications for carbon storage. The relative abundance of pyrite and protokerogen organic sulfur indicates that pyritization is favored at our study site, but this is likely to vary across the spectrum of blue carbon ecosystems.

Elucidating divergent growth and climate vulnerability in abalone (Haliotis iris): A multi-year snapshot - Joanna S. Copedo; Stephen C. Webb; Lizenn Delisle; Ben Knight; Norman L.C. Ragg; Olivier Laroche; Leonie Venter; Andrea C. Alfaro (Marine Environmental Research, 2025)

Use of fecal inoculum from easy and hard keeper horses to determine in vitro digestibility of feedstuffs used in equine diets - L. Bills; G. Webb; A. McGee; C. Webb (Journal of Equine Veterinary Science, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Mindful young brains and minds: a systematic review of the neural correlates of mindfulness-based interventions in youth - Jovan Jande; Isaac N. Treves; Samantha L. Ely; Leah C. Gowatch; Carmen Carpenter; MacKenna Shampine; Christian A. Webb; Matthew D. Sacchet; John D. E. Gabrielli; Hilary A. Marusak (Brain Imaging and Behavior, 2025)

Linking the multiple types of monitoring to the adaptive management cycle to support environmental flows - Xiaoyan Dai; J. Angus Webb; Avril C. Horne; Libby Rumpff; Margaret A. Palmer (Journal of Environmental Management, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Exploring baseline behaviour in group-housed, pre-weaned dairy calves - Sarah E. McPherson; Laura E. Webb; Marie C. McFadden; Anna Flynn; Eddie A.M. Bokkers; Emer Kennedy (Applied Animal Behaviour Science, 2024)

Characterizing variability in geochemistry and mineralogy of western US dust sources - Abby L. Mangum; Gregory T. Carling; Barry R. Bickmore; Nicholas Webb; DeTiare L. Leifi; Janice Brahney; Diego P. Fernandez; Kevin A. Rey; Stephen T. Nelson; Landon Burgener; Joshua J. LeMonte; Alyssa N. Thompson; et al. (Aeolian Research, 2024)

From an accretionary margin to a sediment-rich collision: Spatiotemporal evolution of the magmatism during the closure of the Mongol-Okhotsk Ocean - Susana Henriquez; Ochir Gerel; Sarah Lambart; Cari L. Johnson; Laura E. Webb; Peter C. Lippert (Gondwana Research, 2024)

Controls over Fire Characteristics in Siberian Larch Forests - Elizabeth E. Webb; Heather D. Alexander; Michael M. Loranty; Anna C. Talucci; Jeremy W. Lichstein (Ecosystems, 2024)

Integrating behavioural, material and environmental science to inform the design and evaluation of a reuse system for takeaway food - Maryam Hoseini; Sarah C. Greenwood; Saima Eman; Paul Mattinson; Harriet M. Baird; Rorie Beswick-Parsons; J. Patrick A. Fairclough; Thomas L. Webb; Anthony J. Ryan; Rachael H. Rothman (Resources, Conservation and Recycling, 2024)

Representation of land–atmosphere coupling processes over Africa in coupled model intercomparison project Phase 6 - A. M. Mwanthi; J. N. Mutemi; E. Dyer; R. James; F. J. Opijah; T. Webb; F. Mutua; R. Washington; C. Senior; Z. Segele; G. Artan (Climate Dynamics, 2024)
Climate models are useful tools for monthly to decadal prediction of the evolution of climate. This study assesses how CMIP6 models represent soil moisture-latent heat regimes and coupling processes between the land and atmosphere. Metrics considered are terrestrial and atmospheric coupling indices to show the nature and strength of the coupling over Africa, focusing on the March to May (MAM) and June to August (JJA) seasons over East, Central, and West Africa. Characterization of the annual cycle indicates that model biases are highest during the peak of the rainfall season and least during the dry season, while soil moisture biases correspond with rainfall. Models show appreciable sensitivity to regional characteristics; there was model consensus in representing East Africa and the Sahel as regions of limited soil moisture, while major differences were noted in the wet regime over Central Africa. Most CMIP6 models tend to overestimate the strength of the terrestrial and atmospheric coupling pathways over East and Southern Africa. Inter-model differences in coupling indices could be traced to their inter-annual variability rather than the mean biases of the variables considered. These results encourage further advancement of land surface schemes in the next generation of climate models for a better representation of climate over Africa.

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

The White Hills Gravel of central Victoria: an anomalous Paleogene very coarse-grained fluvial deposit - C. J. Van Praagh; J. A. Webb; S. Q. White (Australian Journal of Earth Sciences, 2024)

Born of fire, borne by water – Review of paleo-environmental conditions, floristic assemblages and modes of preservation as evidence of distinct silicification pathways for silcrete floras in Australia - Andrew C. Rozefelds; John Webb; Raymond J. Carpenter; Anita K. Milroy; Robert S. Hill (Gondwana Research, 2024)

How do plants reduce erosion? An Eco Evidence assessment - A. C. Dahanayake; J. A. Webb; J. Greet; J. D. Brookes (Plant Ecology, 2024)
Soil erosion adversely impacts natural and human environments globally. Vegetation is often used as a sustainable approach to mitigate erosion. Although using vegetation to reduce erosion is a widely accepted concept, how different plant traits mitigate different mechanisms of erosion, and the generality of these mechanisms has not been well demonstrated. We developed ten hypotheses on how different plant traits (roots, leaves, and stems) act to reduce erosion through different mechanisms (binding soil particles, promoting suspended sediment deposition and reducing the energy of waves, runoff, and wind). We then conducted a rapid evidence assessment of the scientific literature using the Eco Evidence method. We found strong evidence to support our overarching hypothesis—an increase in plant abundance reduces erosion. We also found support for the specific hypotheses that plant roots bind soil particles and that greater plant stem density and leaf area reduce surface run-off and promote sediment deposition. There was insufficient evidence to support the hypotheses that an increase in stem density or leaf area reduces wave or wind energy. None of our hypotheses were rejected. Species with higher root and stem densities and greater leaf area will be the most effective in mitigating erosion. Our review highlights that there is insufficient evidence regarding some potentially important mechanisms between vegetation and erosion, making these prospective areas for further research. Our results have the potential to aid environmental engineers when designing schemes to reduce erosion and ecologists and managers who are concerned about the conservation and restoration of erosion-prone environments.

Rubble persistence under ocean acidification threatened by accelerated bioerosion and lower‐density coral skeletons - Alice E. Webb; Ana M. Palacio‐Castro; Kenzie Cooke; Katherine R. Eaton; Benjamin Chomitz; Nash Soderberg; Morgan Chakraborty; Zachary Zagon; Albert Boyd; Patrick M. Kiel; Allyson DeMerlis; Chris T. Perry; et al. (Global Change Biology, 2024)
As the balance between erosional and constructive processes on coral reefs tilts in favor of framework loss under human‐induced local and global change, many reef habitats worldwide degrade and flatten. The resultant generation of coral rubble and the beds they form can have lasting effects on reef communities and structural complexity, threatening the continuity of reef ecological functions and the services they provide. To comprehensively capture changing framework processes and predict their evolution in the context of climate change, heavily colonized rubble fragments were exposed to ocean acidification (OA) conditions for 55 days. Controlled diurnal pH oscillations were incorporated in the treatments to account for the known impact of diel carbonate chemistry fluctuations on calcification and dissolution response to OA. Scenarios included contemporary pH (8.05 ± 0.025 diel fluctuation), elevated OA (7.90 ± 0.025), and high OA (7.70 ± 0.025). We used a multifaceted approach, combining chemical flux analyses, mass alteration measurements, and computed tomography scanning images to measure total and chemical bioerosion, as well as chemically driven secondary calcification. Rates of net carbonate loss measured in the contemporary conditions (1.36 kg m −2 year −1 ) were high compared to literature and increased in OA scenarios (elevated: 1.84 kg m −2 year −1 and high: 1.59 kg m −2 year −1 ). The acceleration of these rates was driven by enhanced chemical dissolution and reduced secondary calcification. Further analysis revealed that the extent of these changes was contingent on the density of the coral skeleton, in which the micro‐ and macroborer communities reside. Findings indicated that increased mechanical bioerosion rates occurred in rubble with lower skeletal density, which is of note considering that corals form lower‐density skeletons under OA. These direct and indirect effects of OA on chemical and mechanical framework‐altering processes will influence the permanence of this crucial habitat, carrying implications for biodiversity and reef ecosystem function.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Marginal snowpacks: The basis for a global definition and existing research needs - J.I. López-Moreno; N. Callow; H. McGowan; R. Webb; A. Schwartz; S. Bilish; J. Revuelto; S. Gascoin; C. Deschamps-Berger; E. Alonso-González (Earth-Science Reviews, 2024)

A new framework for evaluating dust emission model development using dichotomous satellite observations of dust emission - Mark Hennen; Adrian Chappell; Nicholas P. Webb; Kerstin Schepanski; Matthew C. Baddock; Frank D. Eckardt; Tarek Kandakji; Jeffrey A. Lee; Mohamad Nobakht; Johanna von Holdt (Science of The Total Environment, 2024)

Histopathological investigation of four populations of abalone (Haliotis iris) exhibiting divergent growth performance - Joanna S. Copedo; Stephen C. Webb; Norman L.C. Ragg; Leonie Venter; Andrea C. Alfaro (Journal of Invertebrate Pathology, 2024)

Adaptive thermal responses of captive Nile crocodiles (Crocodylus niloticus) in South Africa - Devon M. Viljoen; Edward C. Webb; Jan G. Myburgh; J. Christoff Truter; Jeffrey W. Lang; Albert Myburgh (Applied Animal Behaviour Science, 2023)

Comparative analysis of animal lifespan - Nicole C. Riddle; Peggy R. Biga; Anne M. Bronikowski; James R. Walters; Gerald S. Wilkinson; Jingyue Ellie Duan; Anthony Gamble; Erica Larschan; Richard P. Meisel; Ritambhara Singh; Ashley Webb (GeroScience, 2023)
Comparative studies of aging are a promising approach to identifying general properties of and processes leading to aging. While to date, many comparative studies of aging in animals have focused on relatively narrow species groups, methodological innovations now allow for studies that include evolutionary distant species. However, comparative studies of aging across a wide range of species that have distinct life histories introduce additional challenges in experimental design. Here, we discuss these challenges, highlight the most pressing problems that need to be solved, and provide suggestions based on current approaches to successfully carry out comparative aging studies across the animal kingdom.

Synergistic soil, land use, and climate influences on wind erosion on the Colorado Plateau: Implications for management - Travis W. Nauman; Seth M. Munson; Saroj Dhital; Nicholas P. Webb; Michael C. Duniway (Science of The Total Environment, 2023)

Histopathological changes in the greenshell mussel, Perna canaliculus, in response to chronic thermal stress - Joanna S. Copedo; Stephen C. Webb; Norman L.C. Ragg; Jessica A. Ericson; Leonie Venter; Alfonso J. Schmidt; Natalí J. Delorme; Andrea C. Alfaro (Journal of Thermal Biology, 2023)

Bioactive (Poly)phenol Concentrations in Plant-based Milk Alternatives in the US Market - A. Kennedy; K. Jiang; E. Grainger; M. Webb; C. Chitchumroonchokchai; K. Riedl; M. Manubolu; S. Clinton (Journal of the Academy of Nutrition and Dietetics, 2023)

Florida-California Cancer Health Equity Center (CaRE2) Community Scientist Research Advocacy Program - B. Hensel; N. Askins; E. Ibarra; C. Aristizabal; I. Guzman; R. Barahona; B. Hazelton-Glenn; J. Lee; Z. Zhang; F. Odedina; D. J. Wilkie; M. C. Stern; et al. (Journal of Cancer Education, 2023)
The Community Scientist Program (CSP), a model connecting researchers with community members, is effective to inform and involve the general population in health-related clinical research. Given the existing cancer disparities among Black/African American and Hispanic/Latino/a populations, more models describing how cancer-related CSPs are designed, implemented, and evaluated are needed. The Florida-California Cancer Research, Education and Engagement (CaRE 2 ) Health Equity Center is a tri-institutional, bicoastal center created to eliminate cancer health disparities among Black/African American and Hispanic/Latino/a populations living in California and in Florida. The CaRE 2 Center created a Community Scientist Research Advocacy (CSRA) training program for community members to become cancer research advocates. The CSRA program is currently a 13-week program conducted 100% virtually with all materials provided in English and Spanish for participants to learn more about prostate, lung, and pancreas cancers, ongoing research at CaRE 2 , and ways to share cancer research throughout their communities. Participants attend didactic lectures on cancer research during weeks 1–5. In week 4, participants join CSRA self-selected groups based on cancer-related topics of interest. Each group presents their cancer-related advocacy project developed during weeks 5–12 at the final session. In this paper, we describe the CaRE 2 Health Equity Center’s CSRA program, share results, and discuss opportunities for improvement in future program evaluation as well as replication of this model in other communities.

Training Community African American and Hispanic/Latino/a Advocates on Prostate Cancer (PCa): a Multicultural and Bicoastal Approach - Carolina Aristizabal; Sandra Suther; Yingwei Yao; Linda S. Behar-Horenstein; Fern Webb; Mariana C. Stern; Lourdes Baezconde-Garbanati (Journal of Cancer Education, 2023)
African American communities are disproportionately impacted by prostate cancer (PCa) compared to other racial/ethnic groups. Whereas the incidence of PCa in Hispanic/Latino men is lower than the incidence in non-Hispanic/Latino White men, Hispanic/Latino men are more likely to be diagnosed with PCa in late stages, and less likely to be knowledgeable about PCa, resulting in significant disparities. We developed, culturally adapted, translated, implemented, and evaluated a PCa Cancer Advocacy Training in African American and Hispanic/Latino/a communities. Culturally and language specific content for African American and Hispanic/Latino/a patients on PCa causes, risk factors, epidemiology, detection, diagnosis, and treatment were delivered through a workshop and simultaneously broadcasted in Spanish in Los Angeles County ( n = 29) and in English in Tallahassee, FL ( n = 9). Pre- and posttest surveys assessed impact. Pre vs post differences were statistically significant in knowledge (5.0 ± 1.6 vs 6.3 ± 1.1) and advocacy intentions (3.9 ± 0.9 vs 4.3 ± 0.8), on correctly identifying warning signs for PCa (50% vs 87%), intent to inform and educate about PCa within the next 3 months (69% vs 95%), to ensure that high-quality research is sensitive to the priorities of patients (63% vs 84%), to help increase patient recruitment, compliance, and retention for clinical trials within the next month (62% vs 84%), intent to engage in PCa patient education within the next 3 months (67% vs 92%), and in engaging in PCa community outreach within the next 3 months (67% vs 94%). There were no significant differences due to race/ethnicity. The Cancer Advocacy Training led to increased knowledge, awareness, and intention to engage in advocacy regarding PCa in the next 3 months. Results suggest that delivering culturally and language specific educational information increases engagement of Hispanic/Latino/a and African American patient/community advocates.

Basic human values drive food choice decision-making in different food environments of Kenya and Tanzania - Christine E. Blake; Eva C. Monterrosa; Krystal K. Rampalli; Abdullah Nurus Salam Khan; Ligia I. Reyes; Shiny Deepika Drew; Paula Dominguez-Salas; Salome A. Bukachi; Mariah Ngutu; Edward A. Frongillo; Elyse Iruhiriye; Amy Webb Girard (Appetite, 2023)

S12-01: Physiologically-Based Kinetic (PBK) Models and Applications In Read-Across - J. Madden; C. Thompson; S. Webb; P. Penson; C. Tan; A. Paini (Toxicology Letters, 2023)

Metal ion content of internal organs in the calorically restricted Wistar rat - Alma I. Santos-Díaz; Jordi Solís-López; Elizabeth Díaz-Torres; José C. Guadarrama-Olmos; Beatriz Osorio; Thomas Kroll; Samuel M. Webb; Marcia Hiriart; Ismael Jiménez-Estrada; Fanis Missirlis (Journal of Trace Elements in Medicine and Biology, 2023)

Identification, transformations and mobility of hazardous arsenic-based pigments on 19th century bookbindings in accessible library collections - Marc Vermeulen; Samuel M. Webb; Susan Russick; Alicia C. McGeachy; Karissa Muratore; Marc S. Walton (Journal of Hazardous Materials, 2023)

Drug Shortages Negatively Impact Health Systems and Bedside Patient Care - Joanne C. Routsolias; Ashley N. Webb (Journal of Medical Toxicology, 2023)

Blood chemistry and biliverdin differ according to reproduction and tourism in a free-living lizard - Susannah S. French; Erin L. Lewis; Kwanho C. Ki; Zachary E. Cullen; Alison C. Webb; Charles R. Knapp; John B. Iverson; Michael W. Butler (Journal of Comparative Physiology B, 2023)

Occurrence of Perkinsus olseni and other parasites in New Zealand black‐footed abalone ( Haliotis iris ) - Farhana Muznebin; Andrea C. Alfaro; Stephen C. Webb (New Zealand Journal of Marine and Freshwater Research, 2023)
The culture of endemic New Zealand black‐footed abalone ( Haliotis iris ) represents a growing aquaculture industry, which is potentially threatened by pathogens and parasites. To identify and characterise health risks, a targeted sampling event was conducted of healthy‐ and unhealthy‐looking abalone (shell deformities, tissue damage and brown creamy substance/fluid in tissues) at a land‐based farm. Histological analysis showed signs of ill health, including disrupted and swollen gills with haemocytosis, ceroid material and parasites, and muscle tissues with focal haemocytosis with parasites. For the first time in H. iris , detailed histological observations, followed by confirmatory in situ hybridisation (ISH) resulted in the identification of Perkinsus olseni (5% prevalence). Scyphidia‐ like ciliates (56%), Sphenophrya‐ like ciliates (5%), unidentified disintegrated ciliates (26%), intracellular bacterial microcolonies (IMCs) (9%), apicomplexan‐like cells (1%) and bacteria (2%) were also identified across organs. There was a significant association between the presence of P. olseni and IMCs. Immunological tissue responses (haemocytosis and ceroid material) and gill pathology were evaluated semi‐quantitatively and were significantly associated with P. olseni . Gross abalone appearance was also significantly associated with P. olseni and unidentified disintegrated ciliates. These findings indicate the types of pathogens and parasites found in cultured H. iris for future health assessment studies of this important aquaculture species.

Community perceptions of ecosystem services and disservices linked to urban tree plantings - Jessi J. Drew-Smythe; Yvonne C. Davila; Christopher M. McLean; Matthew C. Hingee; Megan L. Murray; Jonathan K. Webb; Daniel W. Krix; Brad R. Murray (Urban Forestry & Urban Greening, 2023)

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Perkinsus olseni and other parasites and abnormal tissue structures in New Zealand Greenshell™ mussels (Perna canaliculus) across different seasons - Farhana Muznebin; Andrea C. Alfaro; Stephen C. Webb (Aquaculture International, 2023)
The New Zealand Greenshell™ mussel ( Perna canaliculus ) supports the largest aquaculture industry in the country. However, summer mortality events and potential disease outbreaks may threaten the growth of this industry. As an approach to gauging potential threats through the seasons, a detailed histopathological examination was conducted on 256 adult cultured mussels collected from a farm between April 2018 to September 2019, which covered the austral autumn, winter, spring and summer seasons. Histological sections followed by confirmatory in situ hybridization (ISH) resulted in the identification of Perkinsus olseni at an overall prevalence of 56%. Other parasites and pathogens were identified by histology: apicomplexan parasite X (APX) (78%), copepods ( Pseudomyicola spinosus or Lichomolgus uncus ) (1%), Microsporidium rapuae (1%), intracellular microcolonies of bacteria (IMCs) (2%) and bacilli and cocci bacteria (4%) in gills, mantle, gonads, digestive epithelium and digestive tubules. There was a significant association between P. olseni and APX infection in mussels. This is the first report on seasonal variations of P. olseni and APX in New Zealand Greenshell™ mussel. There was a significant association between seasons and the presence of P. olseni and APX in mussels. A significant positive association between the brown material accumulation and parasites ( P. olseni and APX) and between haemocytosis and P. olseni infections were recorded. A significant association between presence of parasites and health condition (healthy and unhealthy) of mussels was observed. Moreover, a significant association between digestive tubule deterioration (large lumen, with a thin epithelial wall) and P. olseni infection was noted. Therefore, this study provides information regarding the infections of potential parasites and pathogens for the first time in P. canaliculus , their seasonal variations and host-parasite interactions within a commercial farm.

Poultry litter increased irrigated cotton N uptake with limited improvement on 15N-labelled urea recovery over one season - Jackie R. Webb; Rakesh Awale; Wendy C. Quayle (Nutrient Cycling in Agroecosystems, 2023)

Targeting de novo loss-of-function variants in constrained disease genes improves diagnostic rates in the 100,000 Genomes Project - Eleanor G. Seaby; N. Simon Thomas; Amy Webb; Helen Brittain; Ana Lisa Taylor Tavares; J. C. Ambrose; P Arumugam; R Bevers; M Bleda; F Boardman-Pretty; C. R. Boustred; H Brittain; et al. (Human Genetics, 2023)
Background Genome sequencing was first offered clinically in the UK through the 100,000 Genomes Project (100KGP). Analysis was restricted to predefined gene panels associated with the patient’s phenotype. However, panels rely on clearly characterised phenotypes and risk missing diagnoses outside of the panel(s) applied. We propose a complementary method to rapidly identify pathogenic variants, including those missed by 100KGP methods. Methods The Loss-of-function Observed/Expected Upper-bound Fraction (LOEUF) score quantifies gene constraint, with low scores correlated with haploinsufficiency. We applied DeNovoLOEUF, a filtering strategy to sequencing data from 13,949 rare disease trios in the 100KGP, by filtering for rare, de novo, loss-of-function variants in disease genes with a LOEUF score < 0.2. We compared our findings with the corresponding patient’s diagnostic reports. Results 324/332 (98%) of the variants identified using DeNovoLOEUF were diagnostic or partially diagnostic (whereby the variant was responsible for some of the phenotype). We identified 39 diagnoses that were “missed” by 100KGP standard analyses, which are now being returned to patients. Conclusion We have demonstrated a highly specific and rapid method with a 98% positive predictive value that has good concordance with standard analysis, low false-positive rate, and can identify additional diagnoses. Globally, as more patients are being offered genome sequencing, we anticipate that DeNovoLOEUF will rapidly identify new diagnoses and facilitate iterative analyses when new disease genes are discovered.

Forecasting solar photosynthetic photon flux density under cloud cover effects: novel predictive model using convolutional neural network integrated with long short-term memory network - Ravinesh C. Deo; Richard H. Grant; Ann Webb; Sujan Ghimire; Damien P. Igoe; Nathan J. Downs; Mohanad S. Al-Musaylh; Alfio V. Parisi; Jeffrey Soar (Stochastic Environmental Research and Risk Assessment, 2022)
Forecast models of solar radiation incorporating cloud effects are useful tools to evaluate the impact of stochastic behaviour of cloud movement, real-time integration of photovoltaic energy in power grids, skin cancer and eye disease risk minimisation through solar ultraviolet (UV) index prediction and bio-photosynthetic processes through the modelling of solar photosynthetic photon flux density (PPFD). This research has developed deep learning hybrid model (i.e., CNN-LSTM) to factor in role of cloud effects integrating the merits of convolutional neural networks with long short-term memory networks to forecast near real-time (i.e., 5-min) PPFD in a sub-tropical region Queensland, Australia. The prescribed CLSTM model is trained with real-time sky images that depict stochastic cloud movements captured through a total sky imager (TSI-440) utilising advanced sky image segmentation to reveal cloud chromatic features into their statistical values, and to purposely factor in the cloud variation to optimise the CLSTM model. The model, with its competing algorithms (i.e., CNN, LSTM, deep neural network, extreme learning machine and multivariate adaptive regression spline), are trained with 17 distinct cloud cover inputs considering the chromaticity of red, blue, thin, and opaque cloud statistics, supplemented by solar zenith angle (SZA) to predict short-term PPFD . The models developed with cloud inputs yield accurate results, outperforming the SZA -based models while the best testing performance is recorded by the objective method (i.e., CLSTM) tested over a 7-day measurement period. Specifically, CLSTM yields a testing performance with correlation coefficient r = 0.92, root mean square error RMSE = 210.31 μ mol of photons m −2 s −1 , mean absolute error MAE = 150.24 μ mol of photons m −2 s −1 , including a relative error of RRMSE = 24.92% MAP E = 38.01%, and Nash Sutcliffe’s coefficient E NS = 0.85, and Legate and McCabe’s Index LM = 0.68 using cloud cover in addition to the SZA as an input. The study shows the importance of cloud inclusion in forecasting solar radiation and evaluating the risk with practical implications in monitoring solar energy, greenhouses and high-value agricultural operations affected by stochastic behaviour of clouds. Additional methodological refinements such as retraining the CLSTM model for hourly and seasonal time scales may aid in the promotion of agricultural crop farming and environmental risk evaluation applications such as predicting the solar UV index and direct normal solar irradiance for renewable energy monitoring systems.

Genomic tools reveal complex social organization of an invasive large mammal (Sus scrofa) - Chelsea L. Titus; Courtney F. Bowden; Timothy J. Smyser; Stephen L. Webb; James C. Beasley (Biological Invasions, 2022)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Learning from the past: opportunities for advancing ecological research and practice using palaeoecological data - Anne E. Goodenough; Julia C. Webb (Oecologia, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Widespread Use of Migratory Megafauna for Aquatic Wild Meat in the Tropics and Subtropics - Daniel J. Ingram; Margi Prideaux; Nicola K. Hodgins; Heidrun Frisch-Nwakanma; Isabel C. Avila; Tim Collins; Mel Cosentino; Lucy W. Keith-Diagne; Helene Marsh; Matthew H. Shirley; Koen Van Waerebeek; Maximin K. Djondo; et al. (Frontiers in Marine Science, 2022)
Wild animals are captured or taken opportunistically, and the meat, body parts, and/or eggs are consumed for local subsistence or used for traditional purposes to some extent across most of the world, particularly in the tropics and subtropics. The consumption of aquatic animals is widespread, in some places has been sustained for millennia, and can be an important source of nutrition, income, and cultural identity to communities. Yet, economic opportunities to exploit wildlife at higher levels have led to unsustainable exploitation of some species. In the literature, there has been limited focus on the exploitation of aquatic non-fish animals for food and other purposes. Understanding the scope and potential threat of aquatic wild meat exploitation is an important first step toward appropriate inclusion on the international policy and conservation management agenda. Here, we conduct a review of the literature, and present an overview of the contemporary use of aquatic megafauna (cetaceans, sirenians, chelonians, and crocodylians) in the global tropics and subtropics, for species listed on the Appendices of the Convention on the Conservation of Migratory Species of Wild Animals (CMS). We find that consumption of aquatic megafauna is widespread in coastal regions, although to varying degrees, and that some species are likely to be at risk from overexploitation, particularly riverine megafauna. Finally, we provide recommendations for CMS in the context of the mandate of the Aquatic Wild Meat Working Group.

TUBB3 Arg262His causes a recognizable syndrome including CFEOM3, facial palsy, joint contractures, and early-onset peripheral neuropathy - Mary C. Whitman; Brenda J. Barry; Caroline D. Robson; Flavia M. Facio; Carol Van Ryzin; Wai-Man Chan; Tanya J. Lehky; Audrey Thurm; Christopher Zalewski; Kelly A. King; Carmen Brewer; Konstantinia Almpani; et al. (Human Genetics, 2021)

Reproductive trade-offs in the colorado checkered whiptail lizard (Aspidoscelis neotesselatus): an examination of the relationship between clutch and follicle size - Hannah E. Caracalas; S. S. French; S. B. Hudson; B. M. Kluever; A. C. Webb; D. Eifler; A. J. Lehmicke; L. M. Aubry (Evolutionary Ecology, 2021)

Vegetation community changes in European woodlands amid a changing climate: a palaeoecological modelling perspective - Julia C. Webb; Anne E. Goodenough (Community Ecology, 2021)

Early inflammation precedes cardiac fibrosis and heart failure in desmoglein 2 murine model of arrhythmogenic cardiomyopathy - K. E. Ng; P. J. Delaney; D. Thenet; S. Murtough; C. M. Webb; N. Zaman; E. Tsisanova; G. Mastroianni; S. L. M. Walker; J. D. Westaby; D. J. Pennington; R. Pink; et al. (Cell and Tissue Research, 2021)
The study of a desmoglein 2 murine model of arrhythmogenic cardiomyopathy revealed cardiac inflammation as a key early event leading to fibrosis. Arrhythmogenic cardiomyopathy (AC) is an inherited heart muscle disorder leading to ventricular arrhythmias and heart failure due to abnormalities in the cardiac desmosome. We examined how loss of desmoglein 2 ( Dsg2 ) in the young murine heart leads to development of AC. Apoptosis was an early cellular phenotype, and RNA sequencing analysis revealed early activation of inflammatory-associated pathways in Dsg2 -null ( Dsg2 −/− ) hearts at postnatal day 14 (2 weeks) that were absent in the fibrotic heart of adult mice (10 weeks). This included upregulation of iRhom2/ADAM17 and its associated pro-inflammatory cytokines and receptors such as TNFα, IL6R and IL-6. Furthermore, genes linked to specific macrophage populations were also upregulated. This suggests cardiomyocyte stress triggers an early immune response to clear apoptotic cells allowing tissue remodelling later on in the fibrotic heart. Our analysis at the early disease stage suggests cardiac inflammation is an important response and may be one of the mechanisms responsible for AC disease progression.

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Competing reproductive and physiological investments in an all-female lizard, the Colorado checkered whiptail - Lise M. Aubry; Spencer B. Hudson; Bryan M. Kluever; Alison C. Webb; Susannah S. French (Evolutionary Ecology, 2020)

Trait‐based ecology at large scales: Assessing functional trait correlations, phylogenetic constraints and spatial variability using open data - Martin A. Wilkes; François Edwards; J. Iwan Jones; John F. Murphy; Judy England; Nikolai Friberg; Daniel Hering; N. LeRoy Poff; Philippe Usseglio‐Polatera; Wilco C. E. P. Verberk; Jon Webb; Lee E. Brown (Global Change Biology, 2020)
The growing use of functional traits in ecological research has brought new insights into biodiversity responses to global environmental change. However, further progress depends on overcoming three major challenges involving (a) statistical correlations between traits, (b) phylogenetic constraints on the combination of traits possessed by any single species, and (c) spatial effects on trait structure and trait–environment relationships. Here, we introduce a new framework for quantifying trait correlations, phylogenetic constraints and spatial variability at large scales by combining openly available species’ trait, occurrence and phylogenetic data with gridded, high‐resolution environmental layers and computational modelling. Our approach is suitable for use among a wide range of taxonomic groups inhabiting terrestrial, marine and freshwater habitats. We demonstrate its application using freshwater macroinvertebrate data from 35 countries in Europe. We identified a subset of available macroinvertebrate traits, corresponding to a life‐history model with axes of resistance, resilience and resource use, as relatively unaffected by correlations and phylogenetic constraints. Trait structure responded more consistently to environmental variation than taxonomic structure, regardless of location. A re‐analysis of existing data on macroinvertebrate communities of European alpine streams supported this conclusion, and demonstrated that occurrence‐based functional diversity indices are highly sensitive to the traits included in their calculation. Overall, our findings suggest that the search for quantitative trait–environment relationships using single traits or simple combinations of multiple traits is unlikely to be productive. Instead, there is a need to embrace the value of conceptual frameworks linking community responses to environmental change via traits which correspond to the axes of life‐history models. Through a novel integration of tools and databases, our flexible framework can address this need.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

A comparison of ocean model data and satellite observations of features affecting the growth of the North Equatorial Counter Current during the strong 1997–1998 El Niño - David J. Webb; Andrew C. Coward; Helen M. Snaith (Ocean Science, 2020)
Descriptions of the ocean's role in the El Niño usually focus on equatorial Kelvin waves and the ability of such waves to change the mean thermocline depth and the sea surface temperature (SST) in the central and eastern Pacific. In contrast, starting from a study of the transport of water with temperatures greater than 28 ∘C, sufficient to trigger deep atmospheric convection, Webb (2018) found that, during the strong El Niños of 1983–1984 and 1997–1998, advection by the North Equatorial Counter Current (NECC) had a much greater impact on sea surface temperatures than processes occurring near the Equator. Webb's analysis, which supports the scheme proposed by Wyrtki (1973, 1974), made use of archived data from a high-resolution ocean model. Previously the model had been checked in a preliminary comparison against SST observations in the equatorial Pacific, but, given the contentious nature of the new analysis, the model's behaviour in key areas needs to be checked further against observations. In this paper this is done for the 1987–1988 El Niño, making use of satellite observations of SST and sea level. SST is used to check the movement of warm water near the Equator and at the latitudes of the NECC. Sea level is used to check the model results at the Equator and at 6∘ N in the North Equatorial Trough. Sea level differences between these latitudes affect the transport of the NECC, the increased transport at the start of each strong El Niño being associated with a drop in sea level at 6∘ N in the western Pacific. Later rises in sea level at the Equator increase the transport of the NECC in mid-ocean. The variability of sea level at 6∘ N is also used to compare the strength of tropical instability waves in the model and in the observations. The model showed that in a normal year these act to dilute the temperature in the core of the NECC. However their strength declined during the development of the strong El Niños, allowing the NECC to carry warm water much further than normal across the Pacific. The results of this paper should not be taken as providing proof of the hypotheses of Wyrtki (1973, 1974) or Webb (2018) but instead as a failure of a targeted study, using satellite observations, to disprove the hypotheses.

Metabolic Niches and Biodiversity: A Test Case in the Deep Sea Benthos - Craig R. McClain; Thomas J. Webb; Clifton C. Nunnally; S. River Dixon; Seth Finnegan; James A. Nelson (Frontiers in Marine Science, 2020)

Dietary inflammatory index, risk and survival among women with endometrial cancer - C. M. Nagle; T. Ibiebele; N. Shivappa; J. R. Hébert; A. B. Spurdle; P. M. Webb (Cancer Causes & Control, 2020)

Do chimpanzees (Pan troglodytes) console a bereaved mother? - Zoë Goldsborough; Edwin J. C. van Leeuwen; Kayla W. T. Kolff; Frans B. M. de Waal; Christine E. Webb (Primates, 2020)

Engaging urban stakeholders in the sustainable management of arthropod pests - Elizabeth C. Lowe; Tanya Latty; Cameron E. Webb; Mary E. A. Whitehouse; Manu E. Saunders (Journal of Pest Science, 2019)

Co-development of a climate change decision support framework through engagement with stakeholders - Anne M. Leitch; J. P. Palutikof; D. Rissik; S. L. Boulter; Fahim N. Tonmoy; S. Webb; A. C. Perez Vidaurre; M. C. Campbell (Climatic Change, 2019)

CoastAdapt: an adaptation decision support framework for Australia’s coastal managers - J. P. Palutikof; D. Rissik; S. Webb; Fahim N. Tonmoy; S. L. Boulter; Anne M. Leitch; A. C. Perez Vidaurre; M. J. Campbell (Climatic Change, 2019)

Overcoming knowledge barriers to adaptation using a decision support framework - J. P. Palutikof; Anne M. Leitch; D. Rissik; S. L. Boulter; M. J. Campbell; A. C. Perez Vidaurre; S. Webb; Fahim N. Tonmoy (Climatic Change, 2019)

Inhibition of Toll-Like Receptor-4 (TLR-4) Improves Neurobehavioral Outcomes After Acute Ischemic Stroke in Diabetic Rats: Possible Role of Vascular Endothelial TLR-4 - Yasir Abdul; Mohammed Abdelsaid; Weiguo Li; R. Clinton Webb; Jennifer C. Sullivan; Guangkuo Dong; Adviye Ergul (Molecular Neurobiology, 2019)

Groundwater as a source of dissolved organic matter to coastal waters: Insights from radon and CDOM observations in 12 shallow coastal systems - Jackie R. Webb; Isaac R. Santos; Damien T. Maher; Douglas R. Tait; Tyler Cyronak; Mahmood Sadat‐Noori; Paul Macklin; Luke C. Jeffrey (Limnology and Oceanography, 2019)
The influence of groundwater and pore‐water exchange on dissolved organic matter (DOM) dynamics in coastal surface waters remains poorly understood. Here, we combine bottom up (i.e., groundwater‐derived flux estimates) and top down (i.e., water column response) evidence to assess whether groundwater exchange drives DOM dynamics in shallow coastal waters. We rely on automated chromophoric DOM (CDOM, a proxy for DOM) and radon ( 222 Rn, groundwater proxy) measurements over tidal time scales in 12 shallow systems, including tidal freshwater wetlands, estuaries, mangroves, coral reefs, coastal lakes, a saltmarsh, and a residential canal estate. Groundwater‐derived dissolved organic carbon (DOC) fluxes ranged from 2 ± 2 mmol m −2 d −1 in a coral reef to 1941 ± 1325 mmol m −2 d −1 in a mangrove tidal creek. These groundwater fluxes replaced surface water DOC inventories on time scales ranging from ~ 0.5 d to several weeks. Systems with short replacement times displayed positive correlations between radon and CDOM in surface waters. Groundwater exchange diluted surface water DOC in four systems. Using multiple lines of evidence, we interpreted groundwater to be an important source of DOM to surface waters in 4 out of the 12 systems, including an offshore coral reef lagoon with low surface water DOC concentrations. Groundwater discharge was a negligible source of DOM in systems with high surface water DOC and CDOM concentrations such as tidal freshwater wetlands and coastal lakes. This investigation highlights the high variability in groundwater‐derived DOC fluxes and responses in the water column, and demonstrates that submarine groundwater discharge and advective pore‐water exchange should be considered in coastal carbon budgets.

Human Neural Stem Cell Extracellular Vesicles Improve Tissue and Functional Recovery in the Murine Thromboembolic Stroke Model - Robin L. Webb; Erin E. Kaiser; Shelley L. Scoville; Tyler A. Thompson; Sumbul Fatima; Chirayukumar Pandya; Karishma Sriram; Raymond L. Swetenburg; Kumar Vaibhav; Ali S. Arbab; Babak Baban; Krishnan M. Dhandapani; et al. (Translational Stroke Research, 2018)

Behavioural responses of an Australian colubrid snake (Dendrelaphis punctulatus) to a novel toxic prey item (the Cane Toad Rhinella marina) - John Llewelyn; Neil C. Choyce; Benjamin L. Phillips; Jonathan K. Webb; David J. Pearson; Lin Schwarzkopf; Richard Shine (Biological Invasions, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Intensive land-based production of red and green macroalgae for human consumption in the Pacific Northwest: an evaluation of seasonal growth, yield, nutritional composition, and contaminant levels - Bradley A. Gadberry; John Colt; Desmond Maynard; Diane C. Boratyn; Ken Webb; Ronald B. Johnson; Gary W. Saunders; Richard H. Boyer (Algae, 2018)

Adaptive Management of Environmental Flows - J. Angus Webb; Robyn J. Watts; Catherine Allan; John C. Conallin (Environmental Management, 2018)

Informing Environmental Water Management Decisions: Using Conditional Probability Networks to Address the Information Needs of Planning and Implementation Cycles - Avril C. Horne; Joanna M. Szemis; J. Angus Webb; Simranjit Kaur; Michael J. Stewardson; Nick Bond; Rory Nathan (Environmental Management, 2018)

Compound-specific amino acid isotopic proxies for distinguishing between terrestrial and aquatic resource consumption - Emily C. Webb; Noah V. Honch; Philip J. H. Dunn; Anna Linderholm; Gunilla Eriksson; Kerstin Lidén; Richard P. Evershed (Archaeological and Anthropological Sciences, 2018)

Metabolic responses to different immune challenges and varying resource availability in the side-blotched lizard (Uta stansburiana) - Geoffrey D. Smith; Lorin A. Neuman-Lee; Alison C. Webb; Michael J. Angilletta; Dale F. DeNardo; Susannah S. French (Journal of Comparative Physiology B, 2017)

Discovery of new orbiviruses and totivirus from Anopheles mosquitoes in Eastern Australia - Agathe M. G. Colmant; Kayvan Etebari; Cameron E. Webb; Scott A. Ritchie; Cassie C. Jansen; Andrew F. van den Hurk; Helle Bielefeldt-Ohmann; Jody Hobson-Peters; Sassan Asgari; Roy A. Hall (Archives of Virology, 2017)

Combined Effects of Experimental Acidification and Eutrophication on Reef Sponge Bioerosion Rates - Alice E. Webb; Steven M. A. C. van Heuven; Didier M. de Bakker; Fleur C. van Duyl; Gert-Jan Reichart; Lennart J. de Nooijer (Frontiers in Marine Science, 2017)

Tissue Contaminant Burdens in San Francisco Estuary White Sturgeon (Acipenser transmontanus): Implications for Population Recovery - Deke T. Gundersen; Steven C. Zeug; Robert B. Bringolf; Joseph Merz; Zachary Jackson; Molly A. H. Webb (Archives of Environmental Contamination and Toxicology, 2017)

Exome sequence genotype imputation in globally diverse hexaploid wheat accessions - Fan Shi; Josquin Tibbits; Raj K. Pasam; Pippa Kay; Debbie Wong; Joanna Petkowski; Kerrie L. Forrest; Ben J. Hayes; Alina Akhunova; John Davies; Steven Webb; German C. Spangenberg; et al. (Theoretical and Applied Genetics, 2017)

Trends in hormone use and ovarian cancer incidence in US white and Australian women: implications for the future - Penelope M. Webb; Adèle C. Green; Susan J. Jordan (Cancer Causes & Control, 2017)

Acute high-caffeine exposure increases autophagic flux and reduces protein synthesis in C2C12 skeletal myotubes - M. A. Hughes; R. M. Downs; G. W. Webb; C. L. Crocker; S. T. Kinsey; Bradley L. Baumgarner (Journal of Muscle Research and Cell Motility, 2017)

Inferring infection hazard in wildlife populations by linking data across individual and population scales - Kim M. Pepin; Shannon L. Kay; Ben D. Golas; Susan S. Shriner; Amy T. Gilbert; Ryan S. Miller; Andrea L. Graham; Steven Riley; Paul C. Cross; Michael D. Samuel; Mevin B. Hooten; Jennifer A. Hoeting; et al. (Ecology Letters, 2017)
Our ability to infer unobservable disease‐dynamic processes such as force of infection (infection hazard for susceptible hosts) has transformed our understanding of disease transmission mechanisms and capacity to predict disease dynamics. Conventional methods for inferring FOI estimate a time‐averaged value and are based on population‐level processes. Because many pathogens exhibit epidemic cycling and FOI is the result of processes acting across the scales of individuals and populations, a flexible framework that extends to epidemic dynamics and links within‐host processes to FOI is needed. Specifically, within‐host antibody kinetics in wildlife hosts can be short‐lived and produce patterns that are repeatable across individuals, suggesting individual‐level antibody concentrations could be used to infer time since infection and hence FOI . Using simulations and case studies (influenza A in lesser snow geese and Yersinia pestis in coyotes), we argue that with careful experimental and surveillance design, the population‐level FOI signal can be recovered from individual‐level antibody kinetics, despite substantial individual‐level variation. In addition to improving inference, the cross‐scale quantitative antibody approach we describe can reveal insights into drivers of individual‐based variation in disease response, and the role of poorly understood processes such as secondary infections, in population‐level dynamics of disease.

Nonsteroidal anti-inflammatory drugs, statins, and pancreatic cancer risk: a population-based case–control study - Pik Fang Kho; Jonathan Fawcett; Lin Fritschi; Harvey Risch; Penelope M. Webb; David C. Whiteman; Rachel E. Neale (Cancer Causes & Control, 2016)

The Variability of Refractivity in the Atmospheric Boundary Layer of a Tropical Island Volcano Measured by Ground-Based Interferometric Radar - G. Wadge; A. Costa; K. Pascal; C. Werner; T. Webb (Boundary-Layer Meteorology, 2016)

Inhibition of Bacterial Toxin Activity by the Nuclear Stain, DRAQ5™ - Joshua N. Webb; Evan Koufos; Angela C. Brown (The Journal of Membrane Biology, 2016)

Immunotherapeutic strategies targeting natural killer T cell responses in cancer - Susannah C. Shissler; Dominique R. Bollino; Irina V. Tiper; Joshua P. Bates; Roshanak Derakhshandeh; Tonya J. Webb (Immunogenetics, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Evaluation of a Porcine Gastric Mucin and RNase A Assay for the Discrimination of Infectious and Non-infectious GI.1 and GII.4 Norovirus Following Thermal, Ethanol, or Levulinic Acid Plus Sodium Dodecyl Sulfate Treatments - Olamide T. Afolayan; Cathy C. Webb; Jennifer L. Cannon (Food and Environmental Virology, 2016)

The effect of prior walking on coronary heart disease risk markers in South Asian and European men - Saravana Pillai Arjunan; Kevin Deighton; Nicolette C. Bishop; James King; Alvaro Reischak-Oliveira; Alice Rogan; Matthew Sedgwick; Alice E. Thackray; David Webb; David J. Stensel (European Journal of Applied Physiology, 2015)

Association between Helicobacter pylori and pancreatic cancer risk: a meta-analysis - Annaka Schulte; Nirmala Pandeya; Jonathan Fawcett; Lin Fritschi; Harvey A. Risch; Penelope M. Webb; David C. Whiteman; Rachel E. Neale (Cancer Causes & Control, 2015)

Projected changes in hailstorms during the 21st century over the UK - M. G. Sanderson; W. H. Hand; P. Groenemeijer; P. M. Boorman; J. D. C. Webb; L. J. McColl (International Journal of Climatology, 2015)
Hailstorms can pose a significant threat to society, by damaging property and disrupting livelihoods. An understanding of how hailstorm characteristics may change under a warming climate is therefore important for assessing the risk of hail damage for the insurance industry. A simple model of hailstone formation has been driven using meteorological data produced by a regional climate model (RCM) to project how hailstorm numbers and hailstone sizes could change during the 21st century in the UK . Evaluation of the modelled hailstone sizes, numbers and spatial distributions showed that they agreed reasonably well with observations. The effect of climate change on the numbers of damaging hailstorms in the UK (hailstones with diameters greater than 15 mm) was then investigated. A downward trend in the total number of damaging hailstorms during the 21st century was projected, with statistically significant trends for hailstones with diameters between 21 and 50 mm. Melting of hailstones made little contribution to the projected reductions. The results are subject to large uncertainties, some of which originate with the convective parameterization scheme used by the climate model.

The effect of the weather on pulmonary exacerbations and viral infections among adults with cystic fibrosis - W. G. Flight; R. J. Bright-Thomas; C. Sarran; K. J. Mutton; J. Morris; A. K. Webb; A. M. Jones (International Journal of Biometeorology, 2014)

Quaternary climatic instability in south‐east Australia from a multi‐proxy speleothem record - M. WEBB; J. DREDGE; P. A. BARKER; W. MÜLLER; C. JEX; J. DESMARCHELIER; J. HELLSTROM; P. M. WYNN (Journal of Quaternary Science, 2014)
Milankovitch‐scale Quaternary climatic oscillations within south‐east Australia are known to be characterized by relatively arid glacial and wet interglacial stages. However, terrestrial proxy records of environmental change are scarce, based largely on river terraces, dune sediments and pollen sequences. Here we present a speleothem‐based palaeoclimate record from Yarrangobilly caves, south‐east Australia. The oxygen isotopic composition of calcite (δ 18 O calcite ) is taken to represent rainfall amount and used as an aridity index. High‐resolution trace element profiles and UV fluorescence support interpretations based on δ 18 O calcite , allowing further designation of key phases of speleothem growth into periods of relative aridity and moisture excess. A hiatus of approximately 37 ka duration divides the record into two key phases of growth which can be mapped onto marine isotope stages 5c–a and 3, respectively. Increasing aridity in the latter half of MIS 5 led to cessation of speleothem growth for the duration of MIS 4. Growth recommences during MIS 3, associated with greater moisture availability, enhanced vegetation and augmented biogeochemical cycling. This speleothem record provides a unique context of terrestrial environmental change and depicts hydrological conditions which fluctuate markedly over the 70‐ka period covering the time of megafauna extinction and human arrival on the continent.

Environmental Flows Can Reduce the Encroachment of Terrestrial Vegetation into River Channels: A Systematic Literature Review - Kimberly A. Miller; J. Angus Webb; Siobhan C. de Little; Michael J. Stewardson (Environmental Management, 2013)

Reliability and importance of structural diversity of climate model ensembles - Tokuta Yokohata; James D. Annan; Matthew Collins; Charles S. Jackson; Hideo Shiogama; Masahiro Watanabe; Seita Emori; Masakazu Yoshimori; Manabu Abe; Mark J. Webb; Julia C. Hargreaves (Climate Dynamics, 2013)

Glyphosate-Based Herbicide Has Contrasting Effects on Prey Capture by Two Co-Occurring Wolf Spider Species - Sandra Rittman; Kerri M. Wrinn; Samuel C. Evans; Alex W. Webb; Ann L. Rypstra (Journal of Chemical Ecology, 2013)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Scaling of standard metabolic rate in estuarine crocodiles Crocodylus porosus - Roger S. Seymour; C. M. Gienger; Matthew L. Brien; Christopher R. Tracy; S. Charlie Manolis; Grahame J. W. Webb; Keith A. Christian (Journal of Comparative Physiology B, 2013)

Effects of intracellular Mn on the radiation resistance of the halophilic archaeon Halobacterium salinarum - Kimberly M. Webb; Jerry Yu; Courtney K. Robinson; Tomiya Noboru; Yuan C. Lee; Jocelyne DiRuggiero (Extremophiles, 2013)

Filtration of sea louse, L epeophtheirus salmonis , copepodids by the blue mussel, M ytilus edulis , and the A tlantic sea scallop, P lacopecten magellanicus , under different flow, light and copepodid‐density regimes - A Bartsch; S M C Robinson; M Liutkus; K P Ang; J Webb; C M Pearce (Journal of Fish Diseases, 2013)
Population management of L epeophtheirus salmonis in C anada currently relies on chemotherapeutants to remove attached stages of the ectoparasite. However, some populations of L . salmonis are developing resistance to chemotherapeutants making alternate management measures necessary. This article explores the ability of filter‐feeding shellfish [ i.e . blue mussels ( Mytilus edulis ) and A tlantic sea scallops ( P lacopecten magellanicus )] to consume the copepodid stages of L . salmonis in the laboratory under static and flowing water conditions, with variable copepodid densities, and with the aid of a light attractant. M ytilus edulis consumed copepodids under both static and flowing water conditions, and the proportion of individuals ingested was similar at low and high copepodid densities, suggesting that M . edulis was not saturated at the concentrations tested. Also, M . edulis consumed more copepodids when a light attractant was present, suggesting that lights may be useful to concentrate widely dispersed copepodids around cultured shellfish in the field. Finally, P . magellanicus consumed the same number of copepodids as an equivalent total wet weight of M . edulis . During each of the four separate experiments, shellfish consumed between 18 and 38% of the copepodids presented per hour, suggesting that both species are well suited for low level removal of copepodids over time.

Rewarding and incentive motivational effects of excitatory amino acid receptor antagonists into the median raphe and adjacent regions of the rat - Sierra M. Webb; Fiori R. Vollrath-Smith; Rick Shin; Thomas C. Jhou; Shengping Xu; Satoshi Ikemoto (Psychopharmacology, 2012)

Climate change scenarios to facilitate stakeholder engagement in agricultural adaptation - N. P. Webb; C. J. Stokes (Mitigation and Adaptation Strategies for Global Change, 2012)

A new large scale soil DNA extraction procedure and real-time PCR assay for the detection of Sclerotium cepivorum in soil - James W. Woodhall; Kathryn M. Webb; Patricia M. Giltrap; Ian P. Adams; Jeff C. Peters; Giles E. Budge; Neil Boonham (European Journal of Plant Pathology, 2012)

Intake of omega-3 and omega-6 fatty acids and risk of ovarian cancer - T. I. Ibiebele; C. M. Nagle; C. J. Bain; P. M. Webb (Cancer Causes & Control, 2012)

Model‐guided fieldwork: practical guidelines for multidisciplinary research on wildlife ecological and epidemiological dynamics - Olivier Restif; David T. S. Hayman; Juliet R. C. Pulliam; Raina K. Plowright; Dylan B. George; Angela D. Luis; Andrew A. Cunningham; Richard A. Bowen; Anthony R. Fooks; Thomas J. O'Shea; James L. N. Wood; Colleen T. Webb (Ecology Letters, 2012)
Infectious disease ecology has recently raised its public profile beyond the scientific community due to the major threats that wildlife infections pose to biological conservation, animal welfare, human health and food security. As we start unravelling the full extent of emerging infectious diseases, there is an urgent need to facilitate multidisciplinary research in this area. Even though research in ecology has always had a strong theoretical component, cultural and technical hurdles often hamper direct collaboration between theoreticians and empiricists. Building upon our collective experience of multidisciplinary research and teaching in this area, we propose practical guidelines to help with effective integration among mathematical modelling, fieldwork and laboratory work. Modelling tools can be used at all steps of a field‐based research programme, from the formulation of working hypotheses to field study design and data analysis. We illustrate our model‐guided fieldwork framework with two case studies we have been conducting on wildlife infectious diseases: plague transmission in prairie dogs and lyssavirus dynamics in A merican and A frican bats. These demonstrate that mechanistic models, if properly integrated in research programmes, can provide a framework for holistic approaches to complex biological systems.

Reliability of multi-model and structurally different single-model ensembles - Tokuta Yokohata; James D. Annan; Matthew Collins; Charles S. Jackson; Michael Tobis; Mark J. Webb; Julia C. Hargreaves (Climate Dynamics, 2012)

The Control of an Invasive Bivalve, Corbicula fluminea, Using Gas Impermeable Benthic Barriers in a Large Natural Lake - Marion E. Wittmann; Sudeep Chandra; John E. Reuter; S. Geoffrey Schladow; Brant C. Allen; Katie J. Webb (Environmental Management, 2012)

Interacting effects of vegetation, soils and management on the sensitivity of Australian savanna rangelands to climate change - Nicholas P. Webb; Chris J. Stokes; Joe C. Scanlan (Climatic Change, 2012)

Late Neogene tectonics in northwestern Victoria: Evidence from the Late Miocene–Pliocene Loxton Sand - T. C. Robson; J. A. Webb (Australian Journal of Earth Sciences, 2011)

Kinrentius , an unusual new leafhopper genus from South America (Hemiptera: Cicadellidae: Deltocephalinae) - CONG WEI; C. H. DIETRICH; M. D. WEBB (Systematics and Biodiversity, 2010)

Viability of cattle sperm under different storage conditions in Cameroon - P. H. Bayemi; I. Leinyuy; V. M. Nsongka; E. C. Webb; A. L. Ebangi (Tropical Animal Health and Production, 2010)

The ears of butterflyfishes (Chaetodontidae): ‘hearing generalists' on noisy coral reefs? - J. F. Webb; J. L. Herman; C. F. Woods; D. R. Ketten (Journal of Fish Biology, 2010)
Analysis of the morphology of all three otolithic organs (sacculus, lagena and utriculus), including macula shape, hair cell morphology, density, orientation pattern, otolith morphology and the spatial relationships of the swimbladder and ear, reveals that butterflyfishes in the genera Chaetodon (which has anterior swimbladder horns) and Forcipiger (which lacks anterior swimbladder horns) both demonstrate the ear morphology typical of teleosts that lack otophysic connections, fishes that have traditionally been considered to be ‘hearing generalists'.

Tea consumption and risk of ovarian cancer - Christina M. Nagle; Catherine M. Olsen; Christopher J. Bain; David C. Whiteman; Adèle C. Green; Penelope M. Webb (Cancer Causes & Control, 2010)

Local people value environmental services provided by forested parks - Navjot S. Sodhi; Tien Ming Lee; Cagan H. Sekercioglu; Edward L. Webb; Dewi M. Prawiradilaga; David J. Lohman; Naomi E. Pierce; Arvin C. Diesmos; Madhu Rao; Paul R. Ehrlich (Biodiversity and Conservation, 2010)

“He said, she said”: who should speak for households about experiences of food insecurity in Bangladesh? - Jennifer C. Coates; Patrick Webb; Robert F. Houser; Beatrice Lorge Rogers; Parke Wilde (Food Security, 2010)

Breastfeeding and risk of epithelial ovarian cancer - Susan J. Jordan; Victor Siskind; Adèle C Green; David C. Whiteman; Penelope M. Webb (Cancer Causes & Control, 2010)

Anisakis nascettii n. sp. (Nematoda: Anisakidae) from beaked whales of the southern hemisphere: morphological description, genetic relationships between congeners and ecological data - Simonetta Mattiucci; Michela Paoletti; Stephen C. Webb (Systematic Parasitology, 2009)

Impact of management interventions on smallholder dairy farms of the western highlands of cameroon - P. H. Bayemi; E. C. Webb; A. Ndambi; F. Ntam; V. Chinda (Tropical Animal Health and Production, 2009)

An integrated method for improving the dairy production sector in developing countries: the case of Cameroon - P. H. Bayemi; E. C. Webb (Tropical Animal Health and Production, 2009)

Slow inactivation of the NaV1.4 sodium channel in mammalian cells is impeded by co-expression of the β1 subunit - Jadon Webb; Fen-fen Wu; Stephen C. Cannon (Pflügers Archiv - European Journal of Physiology, 2009)

Interactions between circadian and hormonal signalling in plants - Fiona C. Robertson; Alastair W. Skeffington; Michael J. Gardner; Alex A. R. Webb (Plant Molecular Biology, 2009)

Prevalence of Brucella abortus antibodies in serum of Holstein cattle in Cameroon - P. H. Bayemi; E. C. Webb; M. V. Nsongka; H. Unger; H. Njakoi (Tropical Animal Health and Production, 2009)

Muscle fiber type characteristics in females with chronic obstructive pulmonary disease. A preliminary study - Howard J. Green; M. E. Burnett; C. D’Arsigny; S. Iqbal; J. Ouyang; K. A. Webb; D. E. O’Donnell (Journal of Molecular Histology, 2009)

Emerging patterns in the comparative analysis of phylogenetic community structure - S. M. VAMOSI; S. B. HEARD; J. C. VAMOSI; C. O. WEBB (Molecular Ecology, 2009)
The analysis of the phylogenetic structure of communities can help reveal contemporary ecological interactions, as well as link community ecology with biogeography and the study of character evolution. The number of studies employing this broad approach has increased to the point where comparison of their results can now be used to highlight successes and deficiencies in the approach, and to detect emerging patterns in community organization. We review studies of the phylogenetic structure of communities of different major taxa and trophic levels, across different spatial and phylogenetic scales, and using different metrics and null models. Twenty‐three of 39 studies (59%) find evidence for phylogenetic clustering in contemporary communities, but terrestrial and/or plant systems are heavily over‐represented among published studies. Experimental investigations, although uncommon at present, hold promise for unravelling mechanisms underlying the phylogenetic community structure patterns observed in community surveys. We discuss the relationship between metrics of phylogenetic clustering and tree balance and explore the various emerging biases in taxonomy and pitfalls of scale. Finally, we look beyond one‐dimensional metrics of phylogenetic structure towards multivariate descriptors that better capture the variety of ecological behaviours likely to be exhibited in communities of species with hundreds of millions of years of independent evolution.

Effects of 12 hour calf withdrawal on conception rate and calf performance of Bos indicus cattle under extensive conditions - R. J. A. Escrivão; E. C. Webb; A. P. J. T. Garcês (Tropical Animal Health and Production, 2009)

Psychological stress during exercise: cardiorespiratory and hormonal responses - Heather E. Webb; Michael L. Weldy; Emily C. Fabianke-Kadue; G. R. Orndorff; Gary H. Kamimori; Edmund O. Acevedo (European Journal of Applied Physiology, 2008)

Increased nitric oxide synthase activity and Hsp90 association in skeletal muscle following chronic exercise - M. Brennan Harris; Brett M. Mitchell; Sarika G. Sood; R. Clinton Webb; Richard C. Venema (European Journal of Applied Physiology, 2008)

Variability of growth, health, and population turnover within mussel beds of Perna canaliculus in northern New Zealand - Andrea C. Alfaro; Steve C. Webb; Claire Barnaby (Marine Biology Research, 2008)

Using Blood Plasma for Monitoring Organochlorine Contaminants in Juvenile White Sturgeon, Acipenser transmontanus, from the Lower Columbia River - D. T. Gundersen; M. A. H. Webb; A. K. Fink; L. R. Kushner; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck (Bulletin of Environmental Contamination and Toxicology, 2008)

Cancers of the esophagus and carbonated beverage consumption: a population-based case–control study - Torukiri I. Ibiebele; Maria Celia Hughes; Peter O’Rourke; Penelope M. Webb; David C. Whiteman (Cancer Causes & Control, 2008)

Mechanisms for the land/sea warming contrast exhibited by simulations of climate change - Manoj M. Joshi; Jonathan M. Gregory; Mark J. Webb; David M. H. Sexton; Tim C. Johns (Climate Dynamics, 2008)

Economic opportunity survey of small scale dairy farms of the north west province of Cameroon - P. H. Bayemi; E. C. Webb; Y. Manjeli; P. Naoussi (Tropical Animal Health and Production, 2007)

Validation of a human progesterone enzyme immunoassay (EIA) kit for use on serum of cattle in Cameroon - P. H. Bayemi; V. M. Nsongka; B. M. A. O. Perera; D. Cavestany; E. C. Webb (Tropical Animal Health and Production, 2007)

Quantitative linkage genome scan for atopy in a large collection of Caucasian families - Bradley T. Webb; Edwin van den Oord; Anthony Akkari; Steve Wilton; Tina Ly; Rachael Duff; Kathleen C. Barnes; Karin Carlsen; Jorrit Gerritsen; Warren Lenney; Michael Silverman; Peter Sly; et al. (Human Genetics, 2007)

Comparison of genetic diversity at microsatellite loci in near‐extinct and non‐endangered species of Mexican goodeine fishes and prediction of cross‐amplification within the family - R. M. Hamill; S. A. Webb; C. Macías Garcia; J. A. Graves; A. E. Magurran; M. G. Ritchie (Journal of Fish Biology, 2007)
The cross‐utility of 12 microsatellite loci (including nine newly developed loci) amongst the viviparous subfamily, the Mexican Goodeinae, was assessed, examining both the probability of amplification and the potential incidence of null alleles from tests of F IS . Genetic diversity was relatively high in comparison to other freshwater species. Amplification success was not correlated with genetic distance between microsatellite source and target species, but taxa that were more distantly related were less likely to be cross‐polymorphic for microsatellite loci. On average, species that were cross‐polymorphic were separated by a genetic distance of 15% at the cytochrome oxidase I locus, while those that were monomorphic were separated by 19%. There was no evidence that null alleles become more frequent at greater source‐target genetic distance.

Transient expression and insertional mutagenesis of Puccinia triticina using biolistics - Craig A. Webb; Les J. Szabo; Guus Bakkeren; Clarke Garry; Richard C. Staples; Merle Eversmeyer; John P. Fellers (Functional & Integrative Genomics, 2006)

On the contribution of local feedback mechanisms to the range of climate sensitivity in two GCM ensembles - M. J. Webb; C. A. Senior; D. M. H. Sexton; W. J. Ingram; K. D. Williams; M. A. Ringer; B. J. McAvaney; R. Colman; B. J. Soden; R. Gudgel; T. Knutson; S. Emori; et al. (Climate Dynamics, 2006)

Mercury Concentrations in Gonad, Liver, and Muscle of White Sturgeon Acipenser transmontanus in the Lower Columbia River - M. A. H. Webb; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck; M. Plumlee; C. Wong; D. T. Gundersen (Archives of Environmental Contamination and Toxicology, 2006)

Evaluation of a component of the cloud response to climate change in an intercomparison of climate models - K. D. Williams; M. A. Ringer; C. A. Senior; M. J. Webb; B. J. McAvaney; N. Andronova; S. Bony; J. -L. Dufresne; S. Emori; R. Gudgel; T. Knutson; B. Li; et al. (Climate Dynamics, 2006)

Gynodioecy in native New Zealand Gaultheria (Ericaceae) - Lynda F. Delph; Curtis M. Lively; C. J. Webb (New Zealand Journal of Botany, 2006)
The breeding systems of Gaultheria native to New Zealand were investigated. Gaultheria antipoda and G. depressa var. depressa populations contained only hermaphrodites. Populations of five other taxa were found to be gynodioecious in natural populations, with 4–67% females, and evidence from the literature and herbarium sheets suggests that an additional five taxa are gynodioecious. Comparisons of flower parts, flower number, and fruit set of females and hermaphrodites in three taxa revealed few significant differences. Corollas of G. paniculata were smaller in females, but style length and flower number per raceme were not significantly different between the two sexes. Flower number per raceme and fruit set also did not differ significantly between females and hermaphrodites of G. crassa and G. oppositifolia. The similarities in fruit set between the sexes (always within 5% of each other within populations), combined with high female frequencies, suggest that male sterility is caused by cytoplasmic factors. Gynodioecy is widespread but not ubiquitous in New Zealand Gaultheria.

Evidence for a new species of Anisakis Dujardin, 1845: morphological description and genetic relationships between congeners (Nematoda: Anisakidae) - Simonetta Mattiucci; Giuseppe Nascetti; Murray Dailey; Stephen C. Webb; Nelio B. Barros; Rossella Cianchi; Luciano Bullini (Systematic Parasitology, 2005)

A reliable method to detect bacterial contamination of blood components using an automated blood culture system - E. Thomas; G. Webb-Young; C. Barth; E. C. Alport; M. V. Kanchana (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

LIMaS: the JAVA-based application and database for microarray experiment tracking - Sarah C. Webb; Anthony Attwood; Tony Brooks; Tom Freeman; Phil Gardner; Clare Pritchard; Debbie Williams; Peter Underhill; Mark A. Strivens; Andy Greenfield; Ekaterina Pilicheva (Mammalian Genome, 2004)

Coffee, Tea and Caffeine and Risk of Epithelial Ovarian Cancer - Susan J. Jordan; David M. Purdie; Adele C. Green; Penelope M. Webb (Cancer Causes & Control, 2004)

Mixing of Stably Stratified Gases in Subsurface Reservoirs: A Comparison of Diffusion Models - C. M. Oldenburg; S. W. Webb; K. Pruess; G. J. Moridis (Transport in Porous Media, 2004)

A floristic analysis of the lowland dipterocarp forests of Borneo - J. W. F. Slik; A. D. Poulsen; P. S. Ashton; C. H. Cannon; K. A. O. Eichhorn; K. Kartawinata; I. Lanniari; H. Nagamasu; M. Nakagawa; M. G. L. Van Nieuwstadt; J. Payne; Purwaningsih; et al. (Journal of Biogeography, 2003)
Aim To (1) identify floristic regions in the lowland (below 500 m a.s.l.) tropical dipterocarp rain forest of Borneo based on tree genera, (2) determine the characteristic taxa of these regions, (3) study tree diversity patterns within Borneo, and (4) relate the floristic and diversity patterns to abiotic factors such as mean annual rainfall and geographical distance between plots. Location Lowland tropical dipterocarp rain forest of Borneo. Methods We used tree (diameter at breast height ≥ 9.8 cm) inventory data from 28 lowland dipterocarp rain forest locations throughout Borneo. From each location six samples of 640 individuals were drawn randomly. With these data we calculated a Sørensen and Steinhaus similarity matrix for the locations. These matrices were then used in an UPGMA clustering algorithm to determine the floristic relations between the locations (dendrogram). Principal coordinate analysis was used to ordinate the locations. Characteristic taxa for the identified floristic clusters were determined with the use of the INDVAL method of Dufrene & Legendre (1997) . Finally, Mantel analysis was applied to determine the influence of mean annual rainfall and geographical distance between plots on floristic composition. Results A total of 77 families and 363 genera were included in the analysis. On average a random sample of 640 trees from a lowland dipterocarp forest in Borneo contains 41.6 ± 3.8 families and 103.0 ± 12.7 genera. Diversity varied strongly on local scales. On a regional scale, diversity was found to be highest in south‐east Borneo and central Sarawak. The most common families were Dipterocarpaceae (21.9% of trees) and Euphorbiaceae (12.2% of trees). The most common genera were Shorea (12.3% of trees) and Syzygium (5.0% of trees). The 28 locations were clustered in geographically distinct floristic regions. This was related to the fact that floristic similarity depended strongly on the geographical distance between plots and similarity in mean annual rainfall. Conclusions We identified five main floristic regions within the lowland dipterocarp rain forests of Borneo, each of which had its own set of characteristic genera. Mean annual rainfall is an important factor in explaining differences in floristic composition between locations. The influence of geographical distance on floristic similarity between locations is probably related to the fact that abiotic factors change with distance between plots. Borneo's central mountain range generally forms an effective dispersal barrier for the lowland tree flora. Diversity patterns in Borneo are influenced by the mid‐domain effect, habitat size and the influence of past climatic changes (ice ages during the Pleistocene).

In Situ Detection of the Pathogen Indicator E. coli Using Active Laser-Induced Fluorescence Imaging and Defined Substrate Conversion - J. Anderson; S. Webb; R. Fischer; C. Smith; J. Dennis; J. Di Benedetto (Journal of Fluorescence, 2002)

Body size and ovarian cancer: case–control study and systematic review (Australia) - David M. Purdie; Christopher J. Bain; Penelope M. Webb; David C. Whiteman; Sandi Pirozzo; Adèle C. Green (Cancer Causes & Control, 2001)

Combining ERBE and ISCCP data to assess clouds in the Hadley Centre, ECMWF and LMD atmospheric climate models - M. Webb; C. Senior; S. Bony; J.-J. Morcrette (Climate Dynamics, 2001)

Amey: A multipurpose, russet-skinned potato cultivar for the Eastern United States - K. G. Haynes; G. A. Porter; B. J. Christ; R. W. Goth; K. O. DeLong; D. E. Halseth; J. B. Sieczka; M. R. Henninger; S. B. Sterrett; G. C. Yencho; R. E. Webb (American Journal of Potato Research, 2001)

Tropical cooling and the isotopic composition of precipitation in general circulation model simulations of the ice age climate - C. D. Charles; D. Rind; R. Healy; R. Webb (Climate Dynamics, 2001)

Gene structure, alternative splicing, and chromosomal localization of pro-apoptotic Bcl-2 relative Bim - Philippe Bouillet; Li Chen Zhang; David C.S. Huang; Graham C. Webb; Cynthia D.K. Bottema; Paul Shore; Helen J. Eyre; Grant R. Sutherland; Jerry M. Adams (Mammalian Genome, 2001)

Boron efficiency in oilseed rape: II. Development of a rapid lab-based screening technique - James C. R. Stangoulis; Michael J. Webb; Robin D. Graham (Plant and Soil, 2000)

Gulf of Mexico Monitoring System - John Blaha; George Born; Norman Guinasso; James Herring; Gregg Jacobs; F. Kelley; Robert Leban; Robert Martin; George Mellor; Peter Niiler; Michael Parke; Richard Patchen; et al. (Oceanography, 2000)

Orthography of some geographical epithets in the New Zealand flora revisited - C. J. Webb; I. Breitwieser; E. Edgar (New Zealand Journal of Botany, 1999)
The use of a Maori place‐name for a specific or infraspecific epithet as a word in apposition is sanctioned by the International Code of Botanical Nomenclature, and this has been the approach adopted to date by most New Zealand botanists. The epithets already published in this form do not require correction. It is recommended that when adopting Maori place‐names as epithets botanists continue to treat Maori place‐names as indeclinable, but clearly explain the origin and form of the epithets chosen.

Physiology of acute silver toxicity in the starry flounder ( Platichthys stellatus ) in seawater - C. Hogstrand; E. A. Ferguson; F. Galvez; J. R. Shaw; N. A. Webb; C. M. Wood (Journal of Comparative Physiology B, 1999)

Isolation and characterization of a Clostridium sp. with cinnamoyl esterase activity and unusual cell envelope ultrastructure - C. S. McSweeney; Amanda Dulieu; Richard I. Webb; Therese Del Dot; Linda L. Blackall (Archives of Microbiology, 1999)

Evidence for polynuclear iron(III) clusters in the root nodule bacterium, Rhizobium leguminosarum bv. viciae WSM710 - Timothy G. St. Pierre; Kerry C. Carson; John Webb; Andrew R. Glenn; Michael J. Dilworth (BioMetals, 1999)

Gender dimorphism in indigenous New Zealand seed plants - C. J. Webb; David G. Lloyd; Lynda F. Delph (New Zealand Journal of Botany, 1999)
The frequent occurrence of gender dimorphism has long been recognised as one of the distinctive features of the New Zealand flora. We list 83 seed plant genera in which gender dimorphism occurs, and document habit, pollination, and dispersal characters for each genus. This means that gender dimorphism is represented in 23% of the genera in the flora; however, not all of these genera are uniformly dimorphic in gender—40% of them include some species or populations that lack gender dimorphism. We estimate that gender dimorphism has arisen autochthonously in 17 of the 83 genera— therefore, gender dimorphism evolved elsewhere in most cases (80%), and was established in New Zealand by subsequent migration. A comparison of the genera in which gender dimorphism occurs with the remainder of the flora shows that gender dimorphism is strongly correlated with fleshy fruits, and with woody habits. No correlation was found between gender dimorphism and pollination mode, perhaps because relatively unspecialised pollination systems are another characteristic feature of the New Zealan flora. Among genera for which gender dimorphism appears to have arisen autochthonously, a liane habit seems to have been a contributing factor, whereas fleshy fruit and pollination mode were not.

Spelling New Zealand in the specific and infraspecific epithets of vascular plants - C. J. Webb; E. Edgar (New Zealand Journal of Botany, 1999)
There is confusion in the botanical literature over the correct forms of epithets used to refer to the country of New Zealand. A table giving original spellings of all specific and infraspecific taxa of vascular plants named after New Zealand is provided, along with corrected spellings and the reasons for these. It is suggested that new names would be more helpful if they were based on character states or habitats that distinguish the taxa being named.

Fine‐scale genetic structuring in a natural population of European wild rabbits ( Oryctolagus cuniculus ) - A. K. SURRIDGE; K. M. IBRAHIM; D. J. BELL; N. J. WEBB; C. RICO; G. M. HEWITT (Molecular Ecology, 1999)
The genetic structure of a free‐living tagged population of European wild rabbits ( Oryctolagus cuniculus ) was investigated for two consecutive years (1990 and 1991) using 10 polymorphic microsatellite loci. A specific social behaviour, the formation of stable breeding groups, influenced the genetic structure of the population. These breeding groups were shown to constitute genetically differentiated units with low levels of gene flow between them. The average relatedness among members of a social group was higher than within the population as a whole. As a result of female philopatry coupled with male‐biased natal dispersal, the relatedness of females was higher than that of males, both within social groups and in the whole population. Furthermore, the average relatedness of females within groups was twice the relatedness of females between groups. This study reveals marked fine‐scale, intrapopulation genetic structure, which is attributable to the social behaviour of the European wild rabbit.

Erratum Inhibition effect of ferric iron on the kinetics of ferrous iron biooxidation - M. Nemati; C. Webb (Biotechnology Letters, 1998)

Inhibition effect of ferric iron on the kinetics of ferrous iron - M. Nemati; C. Webb (Biotechnology Letters, 1998)

Phylogenetic relationships of species of Gingidia and related genera (Apiaceae, subfamily Apioideae) - A. D. Mitchell; C. J. Webb; S. J. Wagstaff (New Zealand Journal of Botany, 1998)
Five genera of Australasian apioid Apiaceae (Gingidia, Scandia, Lignocarpa, Anisotome, and Aciphylla) have a complex taxo‐nomic history with the circumscription of, and inferred relationships among, the currently accepted genera based on only morphological characters. This molecular and phylogenetic study focuses on the relationships among the taxa currently included within Gingidia using the other genera as outgroups. Phylogenetic analyses of nuclear ribosomal DNA internal transcribed spacer region sequences for 17 species from these genera, and comparison with Smyrnium to root the trees, indicate that Gingidia is polyphyletic as currently circumscribed, the species belonging in two distinct monophyletic groups. However, morphological characters do not support these two groups, making taxonomic interpretation difficult. The monophyletic G. montana group includes the ditypic endemic genera Scandia and Lignocarpa, suggesting that they should not be maintained. The second monophyletic group includes G. decipiens and G. flabellata with species of Anisotome. Although our sampling of Anisotome and Aciphylla is limited, nothing in the analysis of the molecular data is inconsistent with earlier suggestions, based on morphological data, that Gingidia, Scandia, Lignocarpa, Anisotome, and Aciphylla form a monophyletic group.

Assignment of the growth hormone receptor gene to band q17 of the homeologous sheep 16 and cattle 20 chromosomes - Yvonne M. Parsons; Graham C. Webb; Cynthia D. K. Bottema (Mammalian Genome, 1998)

A new species of Anisakis Dujardin, 1845 (Nematoda, Anisakidae) from beaked whales (Ziphiidae): allozyme and morphological evidence - Lia Paggi; Giuseppe Nascetti; Steve C. Webb; Simonetta Mattiucci; Rossella Cianchi; Luciano Bullini (Systematic Parasitology, 1998)

Zinc binding to the gills of rainbow trout: the effect of long‐term exposure to sublethal zinc - F. Galvez; N. Webb; C. Hogstrand; C. M. Wood (Journal of Fish Biology, 1998)
The effects of sublethal waterborne Zn (2·28 μmol l −1 ) on Zn binding kinetics to the apical gill surface were studied in juvenile rainbow trout ( Oncorhynchus mykiss ). Two separate radiotracer techniques were employed to ascertain this information. First, in vitro binding kinetic experiments were performed at extremely elevated zinc concentrations (up to 20 mmol l −1 ) to measure relatively low‐affinity binding sites at the gill epithelium. There were no differences in Zn binding parameters ( K m and B max ) for fish sublethally exposed to Zn for 21 days and their simultaneous controls. Nevertheless, Ca did have an increased inhibitory effect on Zn binding in Zn‐exposed fish suggesting that the anionic groups on the gill epithelium of these fish had been altered in some manner. Additionally, in vivo Zn binding kinetics were investigated using environmentally relevant waterborne Zn concentrations (low μmol l −1 range) to isolate high‐affinity Zn binding sites (Ca transporters). No appreciable alterations in the Km and B max values for Zn binding were seen between the Zn‐exposed group and its simultaneous control following 15 days of exposure. Furthermore, no significant differences in CC morphometry were observed between treatments. Despite these lack of treatment effects, there were temporal alterations in K m , B max and CC fractional surface area in both groups. It is proposed that these fluctuations are controlled by hormonal factors (such as stanniocalcin), believed to play a role in Ca influx.

A human homologue of the Drosophila melanogaster sluggish-A (proline oxidase) gene maps to 22q11.2, and is a candidate gene for type-I hyperprolinaemia - H. D. Campbell; Graham C. Webb; Ian G. Young (Human Genetics, 1997)

Evidence of acoustic startle hyperreflexia in recently detoxified early onset male alcoholics: modulation by yohimbine and m -Chlorophenylpiperazine (mCPP) - John H. Krystal; Elizabeth Webb; Christian Grillon; N. Cooney; Lisa Casal; C. A. Morgan III.; Steven M. Southwick; Michael Davis; Dennis S. Charney (Psychopharmacology, 1997)

The reinstatement of Utricularia protrusa for New Zealand and an assessment of the status of the other New Zealand bladderworts based on seed characters - C. J. Webb; W. R. Sykes (New Zealand Journal of Botany, 1997)
Taxonomic views of the genus Utricularia (Lentibulariaceae) as it occurs in New Zealand have changed considerably since the publication of Volume 1 of the Flora of New Zealand in 1961. Examination of the seeds of the New Zealand bladderworts has assisted in further clarifying the status of some species but provides no assistance with others. We now accept three indigenous species for New Zealand: U. protrusa (the name reinstated for plants recently erroneously referred to as U. australis), U. delicatula (a New Zealand endemic distinct from the Australian U. lateriflora) , and U. novae‐zelandiae (including U. monanthos). The name U. gibba (instead of U. biflora) is accepted for the single naturalised species.

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Appendix: A critical examination of rainfall variability measures used in behavioral ecology studies - A. Bronikowski; C. Webb (Behavioral Ecology and Sociobiology, 1996)

Effect of seasonal placement ofCotesia melanoscela (Hym.: Braconidae) on its potential for effective augmentative release againstLymantria dispar (Lep.: Lymantriidae) - A. M. Wieber; R. E. Webb; R. L. Ridgway; K. W. Thorpe; R. C. Reardon; D. M. Kolodny-Hirsch; K. M. Tatman (BioControl, 1995)

Castile: A multiple-purpose, high yielding full-season golden nematode resistant potato variety - D. E. Halseth; J. B. Sieczka; D. D. Moyer; R. W. Goth; R. E. Webb; D. R. Wilson; K. G. Haynes; W. C. Mehlenbacher (American Journal of Potato Research, 1991)

Canopy photosynthesis, stomatal conductance and yield ofSolanum tuberosum grown in a warm climate - Ajmer S. Bhagsari; Raymon E. Webb; Sharad C. Phatak; Casimir A. Jaworski (American Journal of Potato Research, 1988)

The teratogenicity of cadmium-metallothionein in the rat - M. Webb; D. Holt; N. Brown; G. C. Hard (Archives of Toxicology, 1988)

The nature of cadmium binding in commercial Eastern Oysters (Crassostrea virginica) - T. C. Siewicki; J. S. Sydlowski; E. S. Webb (Archives of Environmental Contamination and Toxicology, 1983)

Analysis of malate dehydrogenase isozymes from anuran amphibian ovary by isoelectric focusing - Andrew C. Webb; Hilary M. Ingalls (Biochemical Genetics, 1980)

Delta Gold: A new potato variety with yellow flesh, high solids and high quality for baking and processing - A. F. Reeves; R. E. Webb; D. C. Merriam; H. J. Murphy; F. E. Manzer; R. H. True (American Journal of Potato Research, 1980)

Relative resistance of potato cultivars to bacterial wilt - C. A. Jaworski; R. E. Webb; R. W. Goth; S. C. Phatak (American Journal of Potato Research, 1980)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)

s 59th annual meeting Potato Association of America - D. E. Hudson; M. D. Volz; B. B. DePhillips; Gene A. Mathia; Frank Haynes; N. A. Wynn; Allen E. Abrahams; Lewis A. Schaper; Paul H. Orr; Earl C. Yaeger; Combs Joseph; Robert L. Mercer; et al. (American Journal of Potato Research, 1975)

Report of editorial committee - Arthur Hawkins; Ora Smith; A. Frank Ross; R. E. Webb; G. W. Simpson; J. C. Campbell (American Journal of Potato Research, 1959)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)

Late blight investigations - M. E. Gallegly; Reiner Bonde; C. J. Eide; J. L. Howatt; J. S. Niederhauser; L. C. Peterson; W. R. Mills; R. E. Webb (American Journal of Potato Research, 1958)

Suitability of southern grown potato varieties for processing - William A. Sistrunk; Raymon E. Webb; Julian C. Miller (American Journal of Potato Research, 1954)

Red la soda—A mutation of la soda - R. E. Webb; Julian C. Miller (American Journal of Potato Research, 1954)

Naturally occurring strains of the potato leaf roll virus - R. E. Webb; R. H. Larson; J. C. Walker (American Journal of Potato Research, 1951)

Influence of location on the ascorbic acid content of the Irish potato - John C. Noonan; R. E. Webb; Rita Belle Attaya; Julian C. Miller (American Journal of Potato Research, 1951)